Straw uses trade-off only after soil organic carbon steady-state - Novara, Agata; Sarno, Mauro; Pereira, Paulo; Cerdà, Artemi; Brevik, Eric C.; Gristina, Luciano (Italian Journal of Agronomy, 2018)
Soil organic matter (SOM) is the key for a healthy soil and a relevant property to achieve the sustainability on soil management. However, soils are still net exporters of organic matter. One example is the use of wheat straw residue for industrial and energy applications, which has gained attention in the last years. The offfarm use of this abundant and low cost resource should follow sustainability criteria to avoid soil degradation and SOM losses. Straw residue incorporation is recognized as a recommended management practice to control erosion and mitigate CO2 emissions by increasing SOM. The goal of this work was: i) to evaluate the steady-state carbon (C) level in relation to C input and estimate the minimum residue input needed to maintain this SOC level in a durum wheat-based cropping system in long-term experiment; and ii) estimate the potential availability of durum wheat straws for alternative use. Results showed that a C steady-state can be achieved after 3.4 years with an annual organic C input of 4.5 Mgha–1. Only after reaching a steady-state, straws can be used for trade-off, leaving 1.03 Mgha–1y–1 of C input remain in the soil.